Associations Between Severity of Depression, Lifestyle Patterns, and Personal Factors Related to Health Behavior: Secondary Data Analysis From a Randomized Controlled Trial - Aguilar-Latorre, Alejandra; Serrano-Ripoll, Maria J.; Oliván-Blázquez, Bárbara; Gervilla, Elena; Navarro, Capilla (Frontiers in Psychology, 2022)
Background: Depression is a prevalent condition that has a significant impact on psychosocial functioning and quality of life. The onset and persistence of depression have been linked to a variety of biological and psychosocial variables. Many of these variables are associated with specific lifestyle characteristics, such as physical activity, diet, and sleep patterns. Some psychosocial determinants have an impact on people' health-related behaviour change. These include personal factors such as sense of coherence, patient activation, health literacy, self-efficacy, and procrastination. This study aims to analyze the association between the severity of depression, lifestyle patterns, and personal factors related to health behavior. It also aims to analyze whether personal factors moderate the relationship between lifestyles and depression. Methods: This study is a secondary data analysis (SDA) of baseline data collected at the start of a randomized controlled trial (RCT). A sample of 226 patients with subclinical, mild, or moderate depression from primary healthcare centers in two sites in Spain (Zaragoza and Mallorca) was used, and descriptive, bivariate, multivariate, and moderation analyses were performed. Depression was the primary outcome, measured by Beck II Self-Applied Depression Inventory. Lifestyle variables such as psychical exercise, adherence to Mediterranean diet and sleep quality, social support, and personal factors such as self-efficacy, patient activation in their own health, sense of coherence, health literacy and procrastination were considered secondary outcomes. Results: Low sense of coherence (β = -.172; p < .001), poor sleep quality (β = .179; p = .008), low patient activation (β = -.119; p = .019), and sedentarism (more minutes seated per week) (β = .003; p = .025) are predictors of having more depressive symptoms. Moderation analyses were not significant. Discussion: Lifestyle and personal factors are related to depressive symptomatology. Our findings reveal that sense of coherence, the patient’s activation level, sedentarism, and sleep quality are associated with depression. Further research is needed regarding adherence to Mediterranean diet, minutes walking per week and the interrelationship between lifestyles, personal factors, and depression.